Islamic Law Analysis of Fudhuli Buying and Selling Practices in Panyabungan Market Centre: Between Tradition and Sharia Compliance - Hamid, Asrul; Habibi, Yusuf (Islamic Circle, 2025)
The practice of buying and selling fudhuli is a form of social interaction that occurs at the Panyabungan Market Center in meeting the necessities of life, this is considered a form of mutual assistance among fellow traders to gain profit. Buying and selling fudhuli is the practice of buying and selling by buying and selling other people's goods without getting permission from the owner of the goods. This practice became a problem because it was found that there were defects in the implementation of the sale and purchase. The defects referred to are contained in the terms of sale and purchase. In principle, the conditions for buying and selling must belong to oneself perfectly, but in a fudhuli sale and purchase, the goods being traded still belong to other people and have not received permission from the owner. This study aims to describe the problems related to the practice of buying and selling fudhuli which is mostly carried out at the Panyabungan Market Center in terms of Islamic Law